The Gut–CNS Axis in Multiple Sclerosis - Kadowaki, Atsushi; Quintana, Francisco J. (Trends in neurosciences (Regular ed.), 2020)
Multiple sclerosis (MS) is an autoimmune inflammatory disease of the CNS driven by the inflammatory activity of peripheral immune cells recruited to the CNS and by CNS-resident glial cells. MS pathogenesis has been linked to both genetic and environmental factors. In addition, the commensal flora have been shown to modulate immune processes relevant to MS pathogenesis. We discuss the effects of the gut microbiota on T cells and glial cells, and their relevance for the control of inflammation and neurodegeneration in MS. A better understanding of the gut–CNS axis will shed new light on the mechanisms of disease pathogenesis, and may help to guide the development of efficacious therapies for MS. MS is an autoimmune inflammatory disease characterized by CNS inflammation and damage to myelin.T cells, B cells, and CNS-resident cells including astrocytes and microglia contribute to MS pathogenesis.MS pathogenesis has been linked to genetic and environmental factors, as well as to the gut microbiome.The microbiome modulates the differentiation and function of peripheral immune cells that control CNS inflammation.Microbial metabolites that reach the CNS can modulate the activity of resident glial cells such as astrocytes and microglia.